DM9 Domain Containing Protein Functions As a Pattern Recognition Receptor with Broad Microbial Recognition Spectrum - Jiang, Shuai; Wang, Lingling; Huang, Mengmeng; Jia, Zhihao; Weinert, Tobias; Warkentin, Eberhard; Liu, Conghui; Song, Xiaorui; Zhang, Haixia; Witt, Jennifer; Qiu, Limei; Peng, Guohong; et al. (Frontiers in Immunology, 2017)
DM9 domain was first identified in Drosophila melanogaster, and it was subsequently found to integrate with or without other protein domains across a wide range of invertebrates and vertebrates. In the present study, a member of DM9 domain containing protein (DM9CP) family from marine invertebrate Crassostrea gigas (designated CgDM9CP-1), which was only composed of two DM9 domains, was taken as a protein model to study the biological functions of DM9 domain and its molecular determinants. CgDM9CP-1 was found to exhibit high binding specificity and avidity towards D-mannose residue. It served as a pattern recognition receptor (PRR) with a broad range of recognition spectrum to various pathogen associated molecular patterns (PAMPs), including lipopolysaccharide, peptidylglycan, mannan and β-1, 3-glucan in a D-mannose-dependent manner, as well as bacteria and fungi. In order to reveal the molecular mechanism underlying its pattern recognition activity, the crystal structures of wild type and loss-of-function mutants were solved, and Asp22 and Lys43 were found to be the critical residues for ligand recognition. Moreover, CgDM9CP-1 protein was found to mainly distribute on the surface of C. gigas hemocytes, and it could be translocated into cytoplasm and co-localized with the engulfed microbes during hemocyte phagocytosis. The present result clearly indicated that CgDM9CP-1 was a PRR, and it provided an important clue for the better understanding of DM9CP function.